Gender Differences: Pocket Money Affects Investment Interest with Financial Literacy as a Mediating Variable - Tommy Fedian; Riza Syaputra; Ronald N Girsang; Laula Dwi Martika; Sri Wineh; Gita Suliska (Fakultas Ekonomi Universitas Tridinanti Palembang, 2025)
Investment interest among university students remains relatively low, even though young people have great potential to support the growth of the capital market in Indonesia. This low interest is presumed to be influenced by financial and behavioral factors, such as pocket money and the level of financial literacy, which may differ between males and females. This study aims to analyze the effect of pocket money on students’ investment interest with financial literacy as a mediating variable and to examine the differences in influence based on gender. The research was conducted among students of the Faculty of Economics, Universitas Muara Bungo, involving 247 respondents. A quantitative explanatory approach was employed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) analysis technique with SmartPLS 4.0 software. The findings indicate that pocket money has a significant positive effect on investment interest, and financial literacy partially mediates this relationship. Furthermore, there are differences between male and female students, where males show a stronger direct effect, while females demonstrate a greater mediating role of financial literacy. The limitation of this study lies in its focus on a single university. This research contributes to strengthening financial literacy and developing investment education strategies for students in the fields of economics and finance.